Bahasa dan Wanita dari Ranah Kebangsaan hingga Ranah Dapur: Analisis Linguistik Kontekstual - Ratino Ratino; Kuntoro Kuntoro (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the representation of women in the Indonesian and Javanese languages through a contextual linguistic approach. The analysis focuses on three main domains: the symbolic representation of women in nationalist discourse, gender representation in advertising language, and the semantic shift of domestic vocabulary in Javanese that manifests in the form of pejorative expressions. Employing a descriptive qualitative method, the findings reveal that language functions not only as a tool of communication but also as a means of shaping gender ideology. Terms such as ibu pertiwi (motherland) and ibu kota (capital city) indicate a symbolic appreciation of women’s roles within the national framework. Conversely, diction such as cantik (beautiful) and elegan (elegant) in advertisements reflect socially constructed gender identities. Furthermore, in the Javanese language, the transformation of domestic vocabulary into derogatory expressions—such as kitchen-related terms becoming insults—illustrates a symbolic imbalance concerning women’s domestic roles. This study emphasizes the importance of critical awareness in language use, particularly in shaping inclusive and gender-equal narratives.